EXPLORING OBJECTIVITY IN MODERN RUSSIAN LANGUAGE: A FOCUS ON WORD FORMATION AND GRAMMATICAL MEANINGS - Elmuratova, S.A. (SCIENCE and SOCIETY, 2024)
Objectiveness defines as unmarked part of the meaning in the linguistics. It predetermines complex features of the object. The given article deals with concept of the objectiveness, which is given in different linguists papers.